Development of the Hormone System Material Module as an Effort to Introduce Low Sugar, Salt and Fat Foods to Class XI High School Students - Doholio, Nur Sesya (Journal of Biology Education, 2024)
This Research and Development (R&D) study aimed to describe the validity, practicality, and effectiveness of the hormone system material module to promote low-sugar, low-sodium, and low-fat diets to the eleventh-grade students of senior high school. The samples consisted of 17 students of XI IPA (Eleventh-grade majoring in Natural Science) at SMA Negeri 7 Prasetya Gorontalo. The findings revealed that the validity test obtained a value of 88% with very valid criteria;the practicality test obtained student activity scored 88% with excellent criteria, learning implementation scored 96,6% with excellent criteria, student response questionnaires scored 83% with excellent criteria; and the effectivennes test based on the pre-test and post-test of students learning outcomes obtained a sifnificance value of 0,000 and the n-gain value obtained an average value of 0,70 with high criteria. Therefore, it can be concluded that the modules developed were suitable for use in the learning process.